The Strategy of Small and Medium Enterprises in the Implementation of Green Human Resource Management in Bandung Regency - Ivan Gumilar Sambas Putra; Andhika Ligar Hardhika; Neneng Susanti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Workers as the main actors of SMEs need to understand environmental management as an aspect in order to increase business productivity. Green Human Resource Management (Green HRM) is a tool that can be used to manage the SME workforce by involving environmental aspects. The purpose of this study is to determine the priority of Green HRM criteria for SMEs in Bandung Regency. It is hoped that by producing Green HRM criteria for SMEs and the level of importance for each criterion, strategic steps can be formulated in optimizing Green HRM for SMEs in Bandung Regency. In this research, the research method used is descriptive qualitative method. The method of data collection is done by using a questionnaire with a scale of comparison, interviews and field observations. The data analysis technique was performed using analytical hierarchy process (AHP). The results showed that the implementation of green HRM in SMEs was carried out in an organized manner starting from the recruitment process, selection, training and development, performance evaluation, awards, job descriptions of the workforce and workforce management based on the green concept. Among these processes, the training and development process has the highest weight, which shows it is the most important process in implementing green HRM in SMEs. job description of manpower and manpower management which is based on the green concept. Among these processes, the training and development process has the highest weight which shows it is the most important process in implementing green HRM in SMEs. job description of manpower and workforce management based on the green concept. Among these processes, the training and development process has the highest weight which shows it is the most important process in implementing green HRM in SMEs.